Two-step treatment of dysphagia lusoria: robotic-assisted resection of aberrant right subclavian artery following aortic debranching. (5th July 2020) - La Regina, Davide; Prouse, Giorgio; Mongelli, Francesco; Pini, Ramon
Abstract: A 69-year-old female suffering from severe dysphagia due to an aberrant right subclavian artery was treated with a two-step approach. A right carotid-subclavian bypass was followed 2 weeks later by a robotic-assisted thoracoscopic resection of the aberrant right subclavian artery. The postoperative course was uneventful, and the patient immediately recovered from her dysphagia. In our case, the robotic-assisted technology offered major advantages and, based on our experience, may be useful in the treatment of this rare disease.